2007
DOI: 10.1111/j.1365-4632.2007.03164.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of skin disorders in human immunodeficiency virus‐infected patients in Singapore and the relationship to CD4 lymphocyte counts

Abstract: A preponderance of inflammatory dermatoses and an absence of skin tumors characterized this study. A low CD4 cell count was associated with a higher number of skin disorders and an increased incidence of PPE, psoriasis, and adverse drug eruptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 23 publications
8
73
4
2
Order By: Relevance
“…Seborrheic dermatitis was found to be the common non-infectious dermatoses by studies done by Munoz-Perez MA et al, Singh H et al and Sharma YK et al (18,20,21 ) , but studies by Goh BK et al and Chawhan SM et al (22,23) showed papular pruritic eruption as the common dermatoses. The prevalence of pigmentary disorders in our study was 5.1% and xerosis 4.5%.…”
Section: Discussionmentioning
confidence: 96%
“…Seborrheic dermatitis was found to be the common non-infectious dermatoses by studies done by Munoz-Perez MA et al, Singh H et al and Sharma YK et al (18,20,21 ) , but studies by Goh BK et al and Chawhan SM et al (22,23) showed papular pruritic eruption as the common dermatoses. The prevalence of pigmentary disorders in our study was 5.1% and xerosis 4.5%.…”
Section: Discussionmentioning
confidence: 96%
“…In our patients, seborrheic dermatitis was observed in all stages of HIV infection. Very high incidences of psoriasis have been reported from Asia (up to 25%) in HIV-infected populations (18). In Western studies, on the other hand, 2%-4% incidences of psoriasis have been published (6).…”
Section: Discussionmentioning
confidence: 99%
“…Go BK et al [11] in Singapore report that out of 96 HIV-infected patients, 70% of patients developed lesions at the time of diagnosis, suggesting that HIV has a direct effect on the onset of psoriasis. This association is probably related to the overexpression of tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) [11] [12].…”
Section: Discussionmentioning
confidence: 99%